Universal mini COI barcode for the identification of fish species in processed products - Sultana, Sharmin; Ali, Md. Eaqub; Hossain, M.A. Motalib; ., Asing; Naquiah, Nina; Sarker, Md. Zaidul Islam (Elsevier, 2018)
Species substitution, the use of a low value fish in place of a high value fish, is the biggest problem in inter- national trade and the leading cause of fraud in the fisheries arena sector. Current DNA barcoding systems have partly solved this problem but also failed in many instances to amplify PCR targets from highly processed products because of the degradation of a longer barcode marker (~ 650 bp). In the present study, a novel mini barcode marker (295 bp) was developed to discriminate fish species in raw and processed states forms. The barcode primers were cross-tested against 33 fish species and 15 other animal species and found to be universal for all the tested fish varieties. When 20 commercial fish products of five different categories were screened, all commercial fish sample yielded positive bands for the novel fish barcode. PCR product was sequenced to retrieve the species IDs that reflected 55% (11/20) of Malaysian fish products were mislabeled.